Association of socio-demographic and dietary factors for metabolic syndrome: A comparative study among tribal and non-tribal population - Jayshri R. Ghate; Anshita Gulati; Akanksha Mishra; Rachita Nanda; Vinay Pandit; Sandip Kumar Chandraker; Suyesh Shrivastava; Ravindra Kumar (Clinical Epidemiology and Global Health, 2025)
Background: Metabolic syndrome is a clustering of hyperglycemia and insulin resistance, hypertension, central obesity and dyslipidemia. Recent studies shows an increasing trend of NCDs among tribal population groups. The aim of this study is to explore the presence of metabolic syndrome in tribal and non-tribal communities living in the same geographical area (Durg district) and to find the associated modifiable risk factors. Methods: The present cross-sectional investigation assessed the prevalence of Metabolic Syndrome among 290 participants from Patan block, Durg district, Chhattisgarh. After taking written informed consent from the participants, socio-demographic data was recorded through structured questionnaire. Overnight fasting blood glucose, lipid profile and Homa-IR levels were measured using standard protocols. Presence of metabolic syndrome was established using NCEP- ATP III criteria. Results: The study revealed that 17.7 % of non-tribal and 14.8 % of tribal had metabolic syndrome. A high prevalence of hypertension was observed for both genders. No significant difference in the prevalence of central obesity, dyslipidemia, hypertension, hyperglycemia and Homa-IR in tribal and non-tribal groups was found. Low education level, marital status and a smaller number of meal per day were significant risk factors for metabolic syndrome in tribal group, whereas general obesity (BMI>25 kg/m2) and alcohol consumption were significant risk factor for metabolic syndrome among non-tribal population. Conclusion: These findings provide valuable insights into metabolic syndrome distribution among tribal and non-tribal groups. Social intervention is recommended to address on alcohol dependence and health education about balanced diet to reduce the prevalence of metabolic syndrome in these groups.